2018
DOI: 10.7150/ijbs.25928
|View full text |Cite
|
Sign up to set email alerts
|

A dual-specific IGF-I/II human engineered antibody domain inhibits IGF signaling in breast cancer cells

Abstract: The insulin-like growth factors (IGFs), IGF-I and IGF-II, are essential for regulating cell growth, differentiation and metastasis of a broad range of malignancies. The IGF-I/II actions are mediated through the IGF receptor type 1 (IGF-1R) and the insulin receptor (IR), which are overexpressed in multiple types of tumors. Here, we have firstly identified a human engineered antibody domain (eAd) from a phage-displayed VH library. The eAd suppressed the signal transduction of IGF-1R mediated by exogenous IGF-I o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…There were no FDA drugs for IGFBP6, FOSB, and WLS. Further analysis showed that these three proteins interact with the well-known BRCA related proteins IGF1 [14][15][16] [14][15][16], FOS [17][18][19] [17][18][19],and WNT1 [20][21][22] [20][21][22], suggested that IGFBP6, FPSB, and FOS might be useful target for BRCA treatment. Survival analysis of the 7 DEGs…”
Section: Discussionmentioning
confidence: 99%
“…There were no FDA drugs for IGFBP6, FOSB, and WLS. Further analysis showed that these three proteins interact with the well-known BRCA related proteins IGF1 [14][15][16] [14][15][16], FOS [17][18][19] [17][18][19],and WNT1 [20][21][22] [20][21][22], suggested that IGFBP6, FPSB, and FOS might be useful target for BRCA treatment. Survival analysis of the 7 DEGs…”
Section: Discussionmentioning
confidence: 99%
“…Anti-IGF-1R mAbs do not inhibit the hybrid receptor IGF-1R/IR-A mediated signaling. Inhibition of IGF-1R signaling can also be bypassed by IGF-II dependent IR-A activation [15,16]. Several types of antibodies, including mAbs, bispecific antibodies, and antibody fragments, against IGF-II have been reported [15][16][17][18], which markedly deactivate the IGF-1R/IR and affect tumor growth.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…In recent nanobodies have demonstrated significant translational potential in cancer therapy [ 36 ]. Nanobodies are the smallest functional antibodies which small size (~ 15 kDa) [ 37 , 38 ]. In certain conditions, there are still defects in the use of monoclonal antibodies (mAbs) in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%